Comparison on nitrosation and anaerobic ammonium oxidation between activated sludge and biofilm from an autotrophic nitrogen removal SBBR - Yu, Qin; Jinsong, Guo; Fang, Fang (Tecnología y ciencias del agua, 2017)
Qin, Y., Guo, J., & Fang, F. (March-April, 2017). Comparison on nitrosation and anaerobic ammonium oxidation between activated sludge and biofilm from an autotrophic nitrogen removal SBBR. Water Technology and Sciences (in Spanish), 8(2), 141-149. Activated sludge and biofilm from a Sequencing Biofilm Batch Reactor (SBBR) were studied to analyze their different roles in autotrophic nitrogen removal process. Results showed that under aerobic conditions, the ammonia oxidation rate of activated sludge was 100% and the maximum rate was 0.23 mgN mgVSS−1 d−1 during a 48 h test cycle. Under the same conditions, the ammonia oxidation rate of the biofilm was 72% and the maximum rate was 0.08 mgN mgVSS−1 d−1. The population of AOB (ammonium oxidizing bacteria) in activated sludge was 1.88×1011 cells/g, 10 times that in biofilm. The TN (total nitrogen) removal rate of activated sludge and biofilm under anaerobic conditions were 37% and 83%, respectively. The rate of anaerobic ammonium oxidation by activated sludge was 0.09 mgN mgVSS−1 d−1 and that of biofilm was 0.22 mgN mgVSS−1 d−1. ANAMMOX (anaerobic ammonium oxidizing bacteria) were the dominant bacteria in terms of cell number in this system, with 2.66×1012 cells/g in biofilm—2.6 times more than in activated sludge. TN was removed mainly by anaerobic ammonium oxidation.